Masalah Pembelajaran Bahasa Arab bagi kelas satu dan pemecahannyadari Bagian peningkatan Bahasa OPPM di Pondok Modern Darussalam Gontor Putri 2 - Gautama Veri Vetiana (al-Ittijah : Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2020)
Modern Islamic Boarding School Darussalam Gontor for girls 2, seeks to succeed in teaching and learning of languages by preparing special movers in language teaching for student known as the OPPM Language enhancement section. It is this section that seeks to improve language in the process of teaching and learning by establishing discipline and conducting various language activities, the new students of this lodge experience difficulties in learning the language and the acquisition because of differences in background of learning goals, lack of language knowledge and lack of confidence in the use of language which is due to fear of being wrong and lacking in fluency, in this case the OPPM language seeks to resolve this problem. This study is classified as descriptive qualitative research using case study design at Modern Islamic boarding school Darussalam Gontor for girls 2, Technique of data collection in this research include observation, interview and documentation. The data should be examined by using triangulation. Based on the results of the analysis of the researchers seen various kinds of problems experienced by the first class and can be drawn two conclusions as follows: 1. Problematic learning arabic language for first grade students: 1) Difficulties in using Arabic because it comes from areas with different dialect 2) Problems in pronunciation are triggered by fear of mistakes and ridicule and lack of language knowledge. 3) Difficulties in Arabic pronunciation due to the lack of vocabulary treasury. From what experienced first grade student a problem of language learning, then the OPPM language section trying to solve. 2. Efforts undertaken by the language part in solving this problematic as follows: 1) Holding an official language motivation program to enrich the knowledge of the language of first class students 2) Conduct inter-group dialogue to train in using language with friends without fear. 3) Through Muhadatsah morning program and instructing student to memorize in order to establish vocabulary in the mind of student. 4) Holding interesting language activities to avoid boredom and language learning and instill a sense of language. 5) Listening to a language song to train good hearing and understanding of the language being heard. The result of this study explained on the problematics of learning Arabic language for first grade students, researchers noticed that this study still has many shortcomings and expect that the OPPM language enchancement section can perform the obligations as well as possible by varying the activities of language with which facilitate student in language learning, as well as advising each other about the activities of the language that runs in the Tent and keep the language intensive. And to the next researcher who will discuss the same discussion of this discussion, to research as well as possible and to complete the shortcomings and can write more fully and for the results of writing can be better.